A STUDY ON THE ABILITY IN WRITING NARRATIVE TEXT BY THE SECOND YEAR STUDENTS OF SMA NEGERI 1 TUALANG PERAWANG - Widya Irfani. A; Fadly Azhar; Jismulatif ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This decriptive research was conducted to find out the writing ability in narrative text. The sample of this research was 60 participants from the second year students of SMA Negeri 1 Tualang Perawang by using cluster random sampling technique. The instruments used in this research was writing test. The data were analyzed by calculating students’ score individually and finding out the mean score by using SPSS version 23.0. The data were presentated by using table and bar graph. The researche findings showed that the students’s writing ability was in Poor Category (39.12). So, it was suggested that the students should be more active in taking part in writing activities not only during learning activities in the classroom but also outside the classroom. Then, teacher need motivate the students to do more practice in writing esspecially in narrative text.Key words: Ability, Writing, Narrative Text